2019
DOI: 10.3389/fimmu.2019.00884
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Marrow Edema Links to an Osteoclastic Environment and Precedes Synovitis During the Development of Collagen Induced Arthritis

Abstract: Objectives: To determine the relationship between bone marrow edema (BME), synovitis, and bone erosion longitudinally using a collagen induced arthritis mice (CIA) model and to explore the potential pathogenic role of BME in bone erosion. Methods: CIA was induced in DBA/1J mice. BME and corresponding clinical symptoms of arthritis and synovitis during the different time points of CIA development were assayed by magnetic resonance imaging (MRI), arthritis sore, and histologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“… 48 An elevated number and distribution of osteoclasts adjacent to the trabeculae are representative phenomena in SBMLs. 49 Subsequent remodeling processes are associated with angiogenesis and nerve growth, and the inhibition of osteoclast activity, angiogenesis or even nerve growth in subchondral bone marrow lesion sites might have potential therapeutic effects against both OA progression and pain. Siebelt et al revealed that the subcutaneous injection of alendronate reduces both bone turnover and osteoarthritis progression.…”
Section: Subchondral Bone Microenvironment In Oamentioning
confidence: 99%
“… 48 An elevated number and distribution of osteoclasts adjacent to the trabeculae are representative phenomena in SBMLs. 49 Subsequent remodeling processes are associated with angiogenesis and nerve growth, and the inhibition of osteoclast activity, angiogenesis or even nerve growth in subchondral bone marrow lesion sites might have potential therapeutic effects against both OA progression and pain. Siebelt et al revealed that the subcutaneous injection of alendronate reduces both bone turnover and osteoarthritis progression.…”
Section: Subchondral Bone Microenvironment In Oamentioning
confidence: 99%
“…The reason for this dichotomy is not clear. Differences in a 2A -AR mRNA stability in osteoblasts may contribute to differences in bone remodeling and bone loss (77,104). Moreover, sensory or parasympathetic nerves may also be contributory, as they are involved in the pathology of AA and RA (4,34,105).…”
Section: Sh1293 Did Not Prevent Arthritis-induced Sympathetic Nerve Lossmentioning
confidence: 99%
“…However, a growing amount of data indicate that bone marrow also plays an essential role in osteoclast activation and bone destruction in RA. In a mouse model of arthritis, bone marrow pathologies include increased osteoclast differentiation and accumulation [5,6]. In patients with RA, the overexpression of osteoclastogenesis-promoting factors and active de novo forming osteoclasts have been revealed in bone marrow [7][8][9].…”
Section: Introductionmentioning
confidence: 99%